Do toddlers’ levels of cortisol and the perceptions of parents and professional caregivers tell the same story about transition from home to childcare? A mixed method study - Drugli, May Britt; Nystad, Kathrin; Lydersen, Stian; Brenne, Anne Synnøve (Frontiers in Psychology, 2023)
Introduction: Enrolling in childcare represents the first transition in toddlers’ lives and lays the foundation for their well-being in childcare centers going forward. Child cortisol levels may be an indicator of how toddlers themselves experience their introduction to childcare. In the present study, we explored changes in toddler cortisol levels during their first month in childcare and at a three-month follow-up, as well as the perceptions of parents and professional caregivers regarding the toddlers’ settling-in process during the same period. Method: This study used a mixed-method design. Saliva samples were collected from 113 toddlers and their cortisol levels analyzed. Qualitative notes were collected from parents (n = 87) and professional caregivers (n = 101). The data were analyzed using linear mixed model and thematic analyses, respectively. Results: Changes in toddler cortisol levels and their parents’ and professional caregivers’ perceptions of the transition process fit well. Both data sources indicated an easy start in childcare when parents were present, while the first weeks separated from parents seemed quite demanding. After three months, the cortisol levels returned to a low level, while child wellbeing was perceived as high. Discussion: Toddlers need time to adapt to childcare settings. Even if they are well taken care of by their keyworkers during the day, many toddlers are tired and exhausted in the evenings at home, particularly in the first weeks of separation from their parents. Both professional caregivers and parents should be aware of toddlers’ need for emotional support during their transition to childcare.